1974
DOI: 10.1111/j.1365-2141.1974.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion and Gel Filtration Studies in von Willebrand's Disease

Abstract: A study has been made of the plasma levels of factor-VIII clotting activity and factor-VIII related antigen following transfusion in five patients with von Willebrand's disease and one patient with severe haemophilia. All ofthe patients were transfused with cryoprecipitate or an AHG concentrate and their plasma levels of factor-VIII clotting activity and factor-VIII related antigen assayed at intervals after transfusion. In the case of the patients with von Willebrand's disease there was the expected post tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These studies extend earlier findings on the transfusion response of subjects with vWD, human (8,(15)(16)(17)(18)(19) and swine (9,10,20,21 (20), but not tocorrect the bleeding time. Normal plasma infused in swine (9) …”
Section: Discussionsupporting
confidence: 77%
“…These studies extend earlier findings on the transfusion response of subjects with vWD, human (8,(15)(16)(17)(18)(19) and swine (9,10,20,21 (20), but not tocorrect the bleeding time. Normal plasma infused in swine (9) …”
Section: Discussionsupporting
confidence: 77%
“…In this study also the t112 of the second phase of VIII:C seemed to be shorter (Table VI). The curves were so similar, however, that we feel that this difference is of no importance in comparison to the data reported by others for the half-disappearance time of VIII:C and VIIIR:Ag in transfused hemophiliacs (15)(16)(17). Analysis of the survival of VIIIR:Ag in the four transfused hemophiliacs in this study showed that in A.…”
Section: Discussionmentioning
confidence: 43%
“…In this way the biphasic nature of the disappearance curve was discovered. The early data showed some discordance, but more recent studies have shown that the t1/2s are in the range of about [12][13][14][15][16][17][18] h. The introduction of the quantitative assay for VIIIR:Ag using heterologous antisera (2) allowed the analysis of the disappearance of Factor VIII on the basis of VIIIR:Ag. It was then reported that this VIIIR:Ag decreased more slowly than VIII:C after transfusion of normal cryoprecipitate into hemophiliacs (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is seen with cryoprecipitate [9] and plasma [10] and, perhaps most convincingly, with highpurity vWF concentrate [11], with hemophil iac plasma [10], and with serum [12], Lastly, in vitro studies reveal that the half-life of fac tor VIII is shortened in plasma with reduced vWF concentrations [13] and is extremely brief in the culture medium of cells expressing recombinant human factor VIII unless vWF is added to the medium [14]. This paper discusses a mathematical mod el of factor VIII kinetics based upon the pro posed factor VUI-stabilizing function of vWF binding.…”
Section: Introductionmentioning
confidence: 76%